PENGARUH WAKTU AGING TERHADAP KEKERASAN DAN STRUKTUR MIKRO KOMPOSIT Al-Si-Mg/Al2O3 DENGAN METODE STIR CASTING - Salahuddin Junus; Anne Zulfia; Melisa Melisa; Lilis Mariani (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Aluminum composite needs proper aging period to achieve its optimum mechanical properties through precipitation hardening process. In this research, alumina (Al2O3) particulate reinforced aluminum alloy 6061 composite which is fabricated by stir casting method, undergoes T6 treatment in 175°C for 2 hours, 4 hours, 6 hours, and 8 hours. Mechanical properties evaluations such as tensile testing, hardness testing, and wear rate testing; also microstructure and SEM observation are conducted. Research shows that the optimum artificial aging period for the aluminum composite is 6 hours in 175°C. Wear rate decreases after T6 treatment applied. Hardness increases after T6 treatment applied with aging period of 4 and 6 hours. Tensile strength decreases compared to as-cast composite due to formation of void at interface when T6 treatment conducted. Manufacturing factors will affect the mechanical properties of composite. Keywords: Aluminum composite, billet Al.6061, T6, aging period, stir casting